Monetization of forest's service functions for sustainable forest management (2001)
This paper examined the concept of monetization and its importance in valuation of the forest's social and environmental service functions, vis-a.-vis its sustainable management. Various monetization techniques are highlighted and discussed. Some of these include surrogate price and replacement costs or costs avoided, value of production increases, opportunity costs, travel costs, hedonic pricing and contingent valuation method. (CVM). The use of CVM is canvassed for, because of its highly flexible framework for the valuation of virtually all social and environmental benefits. It can also be easily adapted in developing and less developed countries, where inadequacy of data on socio-economic and environmental characteristics make the use of most other valuation techniques problematic. Keen interest in monetization of forest's non- market benefits, will ensure "holistic approach" to conservation of our natural environmental resources.